Upaya Kolaboratif dalam Penanggulangan Penebangan Kayu Illegal di Provinsi Lampung - Muhammad Tegar Aliffaza; Maya Shafira; Fristia Berdian Tamza (International Forum of Researchers and Lecturers, 2025)
Illegal logging causes deforestation, disrupts forest ecosystems, and threatens biodiversity, contributing to climate change by reducing carbon absorption. It also leads to soil erosion and other environmental issues. This study examines the measures taken by the Lampung Provincial Forestry Service to combat illegal logging in the Way Waya Protected Forest, Pringsewu Regency, and the challenges faced in these efforts. Using a normative and empirical legal approach, the study collects data through literature review and interviews with investigators from the Forestry Service, the Lampung Regional Police, and academics. The findings reveal that preventive actions, such as community outreach and education, alongside repressive measures like joint operations, patrols, and law enforcement, are in place. However, technical and social challenges hinder their effectiveness, requiring institutional improvements and better inter-agency collaboration. This study highlights the need for stronger partnerships between the government, communities, and relevant agencies to combat forest crimes. The recommendations aim to improve forest management policies and raise public awareness of forest preservation.